The Relationship between Sleep Deprivation, Mood Disorders and Non-suicidal Self-injury Behavior among Adolescents - Lan, Zhensong; Kee, Pau; Yusof, Hapsah Md; Huang, Xuefang; Zhou, Huiling (Technium Social Sciences Journal, 2022)
[Background] Sleep deprivation is directly linked to the deficits in an individual's emotional regulations. Most of the adolescents, who experience NSSI, actually do so to regulate their emotions. [Methods] To evaluate the existing relationship between sleep deprivations, adolescent’s mood disorders and NSSI, this study adopted a qualitative research evaluation approach with the help of self-report online questionnaires that were administered to a representative sample of respondents in China ranging between 12 to 19 years. [Results] The research found, whether the sample respondents reported engaging in NSSI and finally, emotional or mood disorders witnessed among the adolescents. The perceived "insufficient sleep" was directly linked to the NSSI engagement and the emotional or mood disorders witnessed by adolescents. Additionally, the mediation interventions or analysis strongly revealed that the mood disorders experienced by the adolescents contributed to their NSSI engagement and perceived "insufficient" sleep. The final results of this research study go a long way in revealing that the "sleep" deprivation witnessed by the adolescents may eventually result in risks for NSSI engagement through mood or emotional deregulation. [Limitations] This study adopted a cross-sectional research design that presented study limitations in its ability to predict future NSSI engagement among adolescents. [Conclusions] The findings presented in this research study go a long way in suggesting that insufficient sleep may eventually confer to increased risks for engaging in NSSI through mood dysregulation. Moreover, intelligence gained from this paper may contribute towards the development of treatment and prevention strategies for engaging in NSSI in adolescents.